Jan Lechoń’s and Kazimierz Wierzyński’s Letters (Some Comments Based on the Critical Edition) - Dorosz, Beata (Tematy i Konteksty, 2021)
This paper presents the problems faced by an editor preparing a correspondence dialogue between Jan Lechoń and Kazimierz Wierzyński (237 letters, mainly handwritten, from the years 1941-1956) for a critical edition, such as: its completeness, dating, or the challenge of deciphering the manuscripts. The paper signals some of the appearing motifs and problems in the letters, making an initial attempt to interpret them in the context of both authors’ biographies, as well as historical events (especially the experience of emigration). Moreover, it contains seventeen short poetic pieces written by both poets (poems, epigrams and trifles) which may be found on the pages of those letters. They have been transcribed from the manuscripts and then edited, therefore appearing in print for the very first time in the Polish version of this article in 2011.